2007
DOI: 10.1111/j.1365-2672.2007.03346.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of phospholipid composition inPseudomonas putidaA ATCC 12633 induced by contact with tetradecyltrimethylammonium

Abstract: Aims:  The aim of this work was to establish if the response to tetradecyltrimethylammonium (TDTMA), a representative quaternary ammonium compound (QAC), involves changes in the phospholipid (PL) composition of Pseudomonas putida A ATCC 12633. Methods and Results:  Pseudomonas putida was exposed to 50 mg l−1 of TDTMA for 15 min, and PL composition was analysed. With respect to control values, phosphatidic acid and phosphatidylglycerol increased by 140% and 120%, respectively; cardiolipin decreased about 60%. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Similarly to results found by Tashiro et al (2011) when studying the OMVs of Pseudomonas aeruginosa, we observed that the OMVs produced by P. putida A (ATCC 12633) did not contain PE and that PG was the major glycerophospholipid detected (42.17 % of total PL; Table 1). Different facts indicated PG as the main component of the OMVs released by P. putida in the presence of TTAB: the sixfold increase (up to 120 %) in the content of PG (Table S1, available in the online Supplementary Material; Boeris et al, 2007Boeris et al, , 2009) and the fact that PG has been associated with the attainment of the proper curvature for the release of membrane vesicles (Tashiro et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly to results found by Tashiro et al (2011) when studying the OMVs of Pseudomonas aeruginosa, we observed that the OMVs produced by P. putida A (ATCC 12633) did not contain PE and that PG was the major glycerophospholipid detected (42.17 % of total PL; Table 1). Different facts indicated PG as the main component of the OMVs released by P. putida in the presence of TTAB: the sixfold increase (up to 120 %) in the content of PG (Table S1, available in the online Supplementary Material; Boeris et al, 2007Boeris et al, , 2009) and the fact that PG has been associated with the attainment of the proper curvature for the release of membrane vesicles (Tashiro et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The mode of action of QACs in bacteria relies on the interaction of the surfactant with the lipidic bilayer of the membrane, which leads to the loss of membrane integrity, disruption of transduction energy, inhibition of protein action and subsequent deleterious effects on growth and viability (McDonnell & Russell, 1999;McBain et al, 2004;Gilbert & Moore, 2005). Although the connection between QAC degradation and tolerance is not well known, we have shown that in P. putida A (ATCC 12633) the adaptive response and resistance to the bactericidal activity of the QACs TTAB involves a mechanism that initiates changes to membrane composition (Boeris et al, 2007(Boeris et al, , 2009Heredia et al, 2014). The addition of a non-lethal concentration of TTAB resulted in the immediate fluidification of P. putida A (ATCC 12633) cell membranes.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The phospholipid (PL) composition of Pseudomonas putida A ATCC 12633 cultivated under unstressed culture conditions is similar to that described for other fluorescent Pseudomonas species (Ramos et al, 1997;Albelo & Domenech 1997;Pinkart & White, 1997). However, in the presence of the quaternary ammonium compound tetradecyltrimethylammonium bromide (TTAB), P. putida A ATCC 12633 responds through quantitative changes in its PL composition, with specific variations in the content of phosphatidic acid (PA), PG and CL (Boeris et al, 2007). In addition, in P. putida A ATCC 12633 cells grown with TTAB and exposed to Al 3 Cl, an increase in PC was detected, which led us to propose a physiological role for PC as a temporary reservoir for available Al 3+ through the formation of Al 3+ : PC complexes (Boeris et al, 2009).…”
Section: Introductionmentioning
confidence: 52%